Chromaticity characteristics of soil profiles in the coastal areas of Fujian and Guangdong, southern China and their climatic significance. (10th March 2023) - Tang, Jinmeng; Lü, Bin; Liu, Xin; Du, Jiahao; Chen, Tianyuan; Li, Jiawei
Abstract: In recent years, there has been an increasing interest in the use of soil color as a climatic proxy. We investigated the variation of soil chromaticity parameters in subtropical and tropical coastal areas in China and their relationships with climatic factors (mean annual precipitation and temperature). Latitudinal zonal soil profiles in the coastal areas of Fujian and Guangdong were selected for study, and chromaticity analysis of soil samples was performed using the CIELAB color system. The principal results are as follows: (1) Soil color in the coastal areas of Fujian and Guangdong is mainly controlled by hematite and goethite. Redness ( a ∗ ) varies significantly with depth within the soil profiles, and two types of profile can be defined: type I in which a ∗ decreases with increasing depth within the profile, and type II in which a ∗ increases with increasing depth within the profile. (2) Overall, a ∗, b ∗ (yellowness) and the b ∗ /a ∗ ratio do not show a significant relationship with latitude. The a ∗ of some of the Fujian profiles and the Guangdong soil profiles are significantly negatively correlated with the MAP, the b ∗ /a ∗ of some of the Fujian is highly positively correlated with MAP. A precipitation threshold may exist for both sets of profiles. There is a high correlation coefficient between b ∗ /a ∗ and MAT, and a temperature threshold of ∼23 °C is evident. b ∗ /a ∗ is correlated with MAP and MAT, and it can potentially be used as a climate proxy.